2014
DOI: 10.4172/2168-975x.1000132
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy in the Treatment of Neurological Diseases

Abstract: Before a half century, regeneration of neurons has been admitted as an impossible event. Thus, neurodegenerative disorders (e.g. Parkinson's disease, Alzheimer's disease, multiple sclerosis), vascular events (e.g. stroke) and traumatic diseases (e.g. spinal cord injury) have been admitted as incurable diseases. Afterward, tissue reparative and regenerative potential of stem cell researches for these disorders drew attention of the scientist to replacement therapy. Now, there are hundreds of current experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Stem cell-based therapy is a promising, safe, and effective therapeutic strategy for several neurodegenerative diseases, including AD (Kocaoglu et al 2014;Chang et al 2014;Wernig et al 2008). Stem cellbased-approach is still under development but rapid achievements indicate its therapeutic potential for reversing AD-associated neurodegeneration, as well as, improving cellular and structural functions (Lee et al 2015;Kwak et al 2018).…”
Section: Stem Cell-based Therapy For Admentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cell-based therapy is a promising, safe, and effective therapeutic strategy for several neurodegenerative diseases, including AD (Kocaoglu et al 2014;Chang et al 2014;Wernig et al 2008). Stem cellbased-approach is still under development but rapid achievements indicate its therapeutic potential for reversing AD-associated neurodegeneration, as well as, improving cellular and structural functions (Lee et al 2015;Kwak et al 2018).…”
Section: Stem Cell-based Therapy For Admentioning
confidence: 99%
“…Therefore, regenerative therapy, using stem cells, could be regarded as a promising and safe approach for regeneration of altered or lost cellular functions (Kocaoglu et al 2014). Although the underlying mechanisms of stem cell-based therapy need more clarification, there are several preclinical studies demonstrated encouraging results (Kwak et al 2018).…”
Section: Introductionmentioning
confidence: 99%